Primary osteoarthrosis of the knee in men and women as a result of lifelong physical load from work - Sandmark, H.; Hogstedt, Christer; Vingård, Eva (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study investigated the effect of lifelong physical load from work on the development of knee osteoarthrosis (OA) leading to prosthetic surgery among men and women.' ' METHODS ': 'In a population-based case-referent study, men and women (N=625) who had had prosthetic surgery due to primary tibiofemoral OA were compared with referents (N=548) as to job titles and exposure to physical load in occupational work, housework, and leisure-time activities from 15 to 50 years of age.' ' RESULTS ': 'Male forestry and construction workers, and both male and female farmers ran the highest risk of knee OA. The men had considerably higher exposure to lifting at work, and also to jumps and vibration, than the women. Among the men there was an association between lifting at work [odds ratio (OR) 3.0, 95% confidence interval (95% CI) 1.6-5.5], squatting or knee bending (OR 2.9, 95% CI 1.7-4.9), kneeling (OR 2.1, 95% CI 1.4-3.3), and jumping (OR 2.7, 95% CI 1.7-4.1) with knee OA. Exposure to physically demanding tasks at home, such as taking care of an elderly or handicapped person, was associated with knee OA among the women (OR 2.2, 95% CI 1.3-3.6).' ' CONCLUSION ': 'Working as a farmer or as a construction worker could be associated with the development of knee OA and lead to prosthetic surgery. Men and women differ in the quality and quantity of reported physical load and also in the strength of the risk estimates. A reduction of high physical load at work and at home could probably lower the risk of knee OA later in life.
Keywords: overweight; physically demanding job; population study; prosthetic knee surgery